Preliminary findings on police custody delivery in the twenty-first century: Is it ‘good’ enough? - Skinns, Layla (Policing and society, 2017)
Since the 1980s, police custody in England and Wales has seen the civilianisation and privatisation of key roles formerly performed by police officers and changes to how police custody suites are managed and owned. These changes have been encapsulated in a five-pronged typology of custody suites identified by Skinns et al. Drawing on theories about ‘good’ policing as well as quantitative and qualitative data collected as part of an ongoing study of ‘good’ police custody, this paper provides some preliminary answers to two key questions: Can police custody ever be ‘good’ for suspects and, relatedly, are some types of custody suites likely to be better than others, in this regard? What are the implications for ‘good’ policing? We show that of the five types of custody suites identified in Skinns et al., the ‘unhurried hybrid’ may be particularly beneficial to ‘good’ experiences of police custody; for example, the conditions of custody are better and may facilitate a more trusting relationship between suspects and the police. The data also show that theories about ‘good’ policing are relevant and useful for conceptualising ‘good’ police custody; though of the five dimensions of ‘good’ policing some (e.g. policing as just) are more relevant than others (e.g. policing as crime reduction).